Multidisciplinary management of type 2 inflammation diseases using a screening tool - Palomares, Oscar; Cisneros, Carolina; Ortiz de Frutos, Francisco Javier; Villacampa, José Miguel; Dávila, Ignacio (Frontiers in Allergy, 2024)
Dysregulation of type 2 (T2) immune response leads to an aberrant inflammatory reaction that constitutes the pathophysiological basis of diseases involving various organs. For this reason, several disorders can coexist in a single patient; however, as different specialists often treat these pathologies, T2 dysregulation, particularly when mild, is not always the first diagnostic suspicion. A breakdown in interdisciplinary communication or the lack of adequate tools to detect these entities can delay diagnosis, and this, together with a lack of coordination, can lead to suboptimal care. In this context, a multidisciplinary group of specialists in pneumology, immunology, allergology, dermatology and otorhinolaryngology compiled a list of the cardinal symptoms reported by patients presenting with T2 inflammation-related diseases: asthma, chronic rhinosinusitis, allergic rhinitis, allergic conjunctivitis, IgE-mediated food allergy, atopic dermatitis, eosinophilic oesophagitis, and NSAID-exacerbated respiratory disease (NERD). Using this information, we propose a simple, patient-friendly questionnaire that can be administered at any level of care to initially screen patients for suspected coexisting T2 diseases and referral to the appropriate specialist.